Pengembangan Portal Berita Berbasis Web Responsive dengan Menggunakan Pendekatan Agile Development - Bagus Arif Setiawan; Farid F (Program Vokasi Universitas Negeri Gorontalo, 2026)
The rapid development of information technology demands news media to provide online platforms that are not only content-rich but also optimal and easily accessible across various responsive devices. This research discusses and implements a tested tri-combination of open-source technologies to build a Professional and Responsive News Portal. The PHP programming language is used as the core logic (server-side) to handle data processing, authentication, and Content Management System (CMS) mechanisms. MySQL is implemented as the fundamental data management system to ensure the efficiency of storage, retrieval, and management of structured and massive news data. Meanwhile, the Bootstrap Framework is comprehensively applied to the frontend side to create a modern, intuitive, and automatically responsive User Interface across platforms (including desktops, tablets, and smartphones). The development method used is Agile Development, which emphasizes flexibility, collaboration, and iterative development to ensure the system adapts quickly to changing user needs. The result of this implementation is a news portal that features fast performance, adaptive layout, and a user-friendly CMS, enabling information accessibility and competitiveness in the digital media landscape.